Analysis of Student Retention in Grade XI at MAN 1 Makassar in Biology Learning - Miftahul Janna; Muhiddin Palennari; Arsad Bahri (Biology Teaching and Learning, 2026)
Abstract Purpose: This study aims to examine long-term retention in Biology learning and identify differences in retention between male and female eleventh-grade students.Research Methodology: This study used a descriptive quantitative design involving eleventh-grade students. Data were collected through post-tests and re-tests using multiple-choice questions as the research instrument. The study measured students’ long-term retention in Biology learning. Data analysis was conducted using descriptive statistics and an independent sample t-test to determine gender differences in retention scores.Results: The findings showed that most students had low retention levels. A total of 119 students (69.6%) were categorized as low retention, 34 students (20.5%) as moderate retention, and only 18 students (9.9%) as high retention. The t-test analysis produced a significance value of 0.00 (<0.05), indicating a significant difference between male and female students. Female students achieved higher average retention scores (57.54%) than male students (50.78%).Conclusions: Biology retention among eleventh-grade students is generally low, and gender significantly influences retention outcomes. Female students tend to retain Biology concepts better than male students.Limitations: This study was limited to eleventh-grade students and applied only a descriptive quantitative approach, limiting broader generalization.Contributions: This study contributes to Biology education by providing empirical evidence regarding long-term retention and gender differences. The findings can help teachers, schools, and researchers develop effective learning strategies to improve students’ conceptual understanding and retention.Keywords: Biology learning, Gender differences, Retention